Baby food chair for autism kids / Zarina Begum Ebrahim … [et al.] - Ebrahim, Zarina Begum; Zulkefii, Nur Zafirah; Azhar, Nurul Huda Najihah; Azmani, Nurul Syafiqa; Md Shah, Siti Nor Shahida; Mustakim, Nurul Ain; Sauid, Muna Kameelah; Mokhtar, Noorzalyla (Division of Research and Industry Linkages, 2017)
The Baby Food High Chair was design specifically for autism kids. It was so special when its come to mealtime and also convenience at home or away, Before, the high chair was design just like adult-sized furniture, children’s pieces follow fashions and trends: some are expensive and elaborate, others are throwbacks to an earlier era, and some are more about function than looks. While in 20th century, this baby food chair become popular among newly parents however for special cases such autism's baby, we never found any suitable chair for them. Thus, this chair was design for this baby because children with autism have social, communication and language problems. They have difficulty in communicate with other people or to socialize. They also have restricted and repetitive patterns of behavior, interests, or activities. Autism spectrum disorder may lead to aggression and self-injury. Hence, we have make an objective that is to make the baby feel more comfortable with the special chair, to prevent neck injuries caused by repetitive activities, and to. show the world how important to choose the right chair for autism’s baby and to give the baby joyful when sit on the chair. The chair was also design with special spectrum to attract the attention of baby to be sitted in the chair. It always a disaster for many parents who have autism baby when it comes to meal time. It is because the autism kid tend to be hyper and cannot be placed at one point for a longer time. By designing this chair, it was believed the problem of most parent will decrease.